POLA MODEL-V SEBAGAI PENYALURAN PUPUK BERSUBSIDI KEPADA KELOMPOK TANI KECAMATAN SINGARAN PATI - Muhammad Rizky; Ujang Juhardi; Yovi Apridiansyah; AR. Wallad Mahfuzi (UNIVED Press, 2024)
PT Pupuk Sriwidjaja Palembang (Pusri) is a company founded as a pioneer producer of urea fertilizer in Indonesia on December 24 1959 in Palembang, South Sumatra, under the name PT Pupuk Sriwidjajad(Persero). The system development model used in this research is the V-model. V-model which consists of development stages (requirements analysis, specification analysis, design, and implementation) and testing stages (unit testing, integration testing, system testing, and acceptance testing). The method used in system development is the V-Model. This method uses parameters in the form of transportation origin (retailer), and transportation destination (farmers), followed by the process of calculating the amount of fertilizer allocation which has been divided according to the planting period, namely 3 per farmer group which gives results in the form of recommendations for distribution transportation costs. Based on previous system developments that use The V-Model method can be concluded that the intelligence/investigation that has been carried out regarding the occurrence of fraud so that the distribution of fertilizer in the Singaran Pati sub-district is not optimal is incorrect. The V-Model is one of the SDLCs which is the result of a variation of the waterfall model and is described in the form of V. Model -V is a method intended for small to medium-scale teams. This methodology allows software development to save costs and time required for project realization. Constant feedback is also a strong side. It's important to listen and make any necessary changes promptly.